Performance and cholesterol of quail egg yolks fed with rice bran raw material with mangosteen peel flour enrichment - Ralahalu, Tabita Naomi; Fredriksz, Shirley; Matatula, Michel J. (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2024)
This study aimed to examine the use of rice bran with enriched mangosteen rind in feed on the performance and cholesterol of quail egg yolks. The cage as a research tool was modified with ram wire on four sides, and a base with dimensions per box, length 59 cm, width 55 cm, height and base 30 cm. 15 food containers made of zinc measuring 48 x 6 x 6 cm were placed outside the cage. Using 15  bottles plastic at 800cc brand Medion as drinking bottles, Harnic HL3650 digital scales with an accuracy 1 gram for weighing feed, and HWH DJ602B digital scales with an accuracy of 0.01 gram for weighing eggs. The study used a completely randomized design with  3 treatments  and  5 replications, with ten quails in each unit. The treatments tested were DP0 = control feed, DP1 = feed plus rice bran enriched with mangosteen peel flour without storage, and DP2 = feed plus rice bran enriched with mangosteen peel flour which is stored for 1 month. The mean differences between treatments were analyzed using the BNT test. The variables observed were feed intake, body weight gain, feed conversion, and egg yolk cholesterol. The results showed that the treatment given was significantly different (P<0.05) on feed intake, while body weight gain, feed conversion, and egg yolk cholesterol were not significantly different (P>0.05). The amount of feed consumed by quail fed rice bran with enriched mangosteen peel flour had different responses. The smallest amount consumed was found in the DP1 test feed. However, regarding weight gain, feed conversion and egg yolk cholesterol, the experimental feed did not show a good response. Homemade feed is 40.9% more expensive than commercial BR I broiler chicken feed.